ANALYSIS OF NETWORK LOAD BALANCING IMPLEMENTATION WITH EQUAL COST MULTI PATH METHOD - Stefanus Eko Prasetyo; Jimmy Cung (Universitas Internasional Batam, 2022)
Internet Service Providers (ISPs) provide internet services, both for local and international internet connections. The need for internet bandwidth is increasing day by day, sometimes 1 ISP is not enough to support our needs. In some large companies that rely heavily on internet access, of course they have several internet providers for network backups when one ISP goes down. One way of implementing backup and merging of Internet ISP lanes requires load balancing techniques. The method used is Equal Cost Multi Path which is a load balancing technique that uses a per addresspair connection load balancing method. ECMP allows routers to have more than one gateway for a single destination network. This method can be useful to overcome if one ISP is disconnected it will be able to be replaced by a second ISP so that the internet is not immediately lost. The results obtained after implementing ECMP load balancing, companies and users will continue to be connected to the internet, and work will not be interrupted when the main ISP is down